Kepemimpinan Digital Menghadapi Persaingan Global Di Perguruan Tinggi - Anwar, Sholihul (JURNAL PEDAGOGY, 2023)
A leader is a person in a group who has a combination of personality and leadership skills that make others want to follow his direction. There are 5 leadership styles according to the leadership grid, namely the middle style, mid, relaxed and work. In the era of fast-paced scientific and technological progress and the digital era, today's leaders must also be able to compete in creating digitally literate leadership. By transforming employees digitally and digital tools (tools) become one of the effective strategies to stay quality and superior. In reality, there is still educational leadership in universities that have not implemented digital leadership as a form of transformation from faster technological developments. Facts show that not a few universities are climbing and then collapse instantly. Conversely, not a few universities continue tomaintain an increasing trend of performance. This phenomenon is closely related to the influence of globalization. Transformative leaders are able to see challenges into opportunities so that technological advances can be opportunities in implementing digital leadership. There are seven characteristics of digital leadership: responsibility, results, information distribution, purpose and judgment, error and conflict, change, and innovation. Therefore, facing global competition, there are several challenges that are faced in carrying out educational leadership, namely mastery of digital technology, creating new innovations, improving HR qualifications, certification programs, increasing competencies and career development. Keywords: Digital Leadership; Global Competition, Higher Education